Practical reason in law and morality - MacCormick, Neil. (Oxford : Oxford University Press, 2008)
This text offers a clear account of the philosophy of practical reason in ethics and legal theory. It explains how reasons relate to actions, the nature of values and their relation to reasons, and the relation of morality to legal reasoning.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Law -- Moral and ethical aspects; Law and ethics